Pengaruh Persepsi Digital Marketing dan Persepsi Harga Terhadap Kepuasan Pelanggan PT. Avicenna Greenhill Kota Bekasi - Dhaifina, Safira; Santoso, Sugeng (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The research problem addressed in this study is whether perceptions of digital marketing and price perception simultaneously influence customer satisfaction at PT. Avicenna Greenhill, Bekasi City. The objective of this research is to analyze the simultaneous influence of digital marketing perception and price perception on customer satisfaction at PT. Avicenna Greenhill, Bekasi City. This study employs a survey method with a quantitative and correlational approach. The sampling technique used is Simple Random Sampling, with a total of 60 respondents participating in the study. The variables examined in this research are digital marketing perception (X1), price perception (X2), and customer satisfaction (Y). Based on the findings, the following conclusions were drawn: (1) The digital marketing perception variable has a strong and significant positive influence on customer satisfaction, with a correlation coefficient of 0.761. The coefficient of determination is 0.579, indicating that digital marketing perception contributes 57.9% in explaining customer satisfaction. (2) The price perception variable also has a strong and significant positive influence on customer satisfaction, with a correlation coefficient of 0.690. The coefficient of determination is 0.476, meaning that price perception accounts for 47.6% in explaining customer satisfaction. (3) Both digital marketing perception and price perception together have a strong and significant positive influence on customer satisfaction, with a correlation coefficient of 0.786. The coefficient of determination is 0.618, suggesting that these two variables jointly contribute 61.8% to explaining customer satisfaction.